The ‘Push and Pull’ Factors of Distributed Leadership: Exploring Views of Headteachers across Two Countries - Dampson, Dandy George; Frempong, Evelyn Ama (Asian Journal of Education and Training, 2018)
Governments and other stakeholders in education are beginning to recognize the important roles school leaders can play in school development and efforts are being made to allow them to become more involved in managing schools. However, despite these efforts, head teachers are challenged with the perfect leadership style to improve schools. Many scholars have lauded the positives of distributed leadership as one if not the best leadership for school improvement. This study sought to explore distributed leadership across primary schools in Accra-Ghana and Northampton-UK. The study adopted the explanatory sequential mixed method design. In this design, face-to-face interviews and non-participants observations were employed while closed ended questionnaires were given to 65 head teachers and 10 out of the 65 head teachers were sampled and interviewed. Two schools were purposive sampled and observed. The findings of the study revealed that head teachers from both countries understood the concept of distributed leadership as giving leadership opportunity to other teachers to meaningfully accept and take full responsibility for their leadership roles. Despite these findings, head teachers from the two countries have their own style of distributing leadership in the school. Admittedly, head teachers echoed that team work and trust is a necessity for effective and successful distributed leadership in schools. Notwithstanding these benefits of distributed leadership, head teachers from both Northampton and Accra are confronted with some challenges such as who should be involved and to what extent. The researchers recommend that head teachers should find ways of giving freedom to teachers who have the requisite expertise and ready to lead particular areas of the school even if it is for a shorter time. Additionally, a well-structured programme of high quality in-service training should be developed and offered to every head teacher and teacher in order for every school to develop appropriately.